Mixed‐Halide Double Perovskite Cs2AgBiX6 (X=Br, I) with Tunable Optical Properties via Anion Exchange. Issue 20 (2nd September 2021) - Wu, Hua; Erbing, Axel; Johansson, Malin B.; Wang, Junxin; Kamal, Chinnathambi; Odelius, Michael; Johansson, Erik M. J.
Abstract: Lead‐free double perovskites, A2 M + M ′3+ X6, are considered as promising alternatives to lead‐halide perovskites, in optoelectronics applications. Although iodide (I) and bromide (Br) mixing is a versatile tool for bandgap tuning in lead perovskites, similar mixed I/Br double perovskite films have not been reported in double perovskites, which may be due to the large activation energy for ion migration. In this work, mixed Br/I double perovskites were realized utilizing an anion exchange method starting from Cs2 AgBiBr6 solid thin‐films with large grain‐size. The optical and structural properties were studied experimentally and theoretically. Importantly, the halide exchange mechanism was investigated. Hydroiodic acid was the key factor to facilitate the halide exchange reaction, through a dissolution–recrystallization process. In addition, the common organic iodide salts could successfully perform halide‐exchange while retaining high mixed‐halide phase stability and strong light absorption capability. Abstract : Ion exchange : A halide‐exchange method is introduced to narrow the bandgap of double perovskite Cs2 AgBiBr6 solid thin‐films, resulting in over 0.3 eV bandgap change under ambient conditions, with superior stability. Hydroiodic acid is demonstrated to be a key factor to facilitate the anion‐exchange using organic iodide salt, making the proposed method versatile.